Venous Thromboembolism Events Following Venovenous Extracorporeal Membrane Oxygenation for Severe Acute Respiratory Syndrome Coronavirus 2 Based on CT Scans - Parzy, Gabriel (Crit Care Med, 2020)
OBJECTIVES: The main objective of the study was to determine the prevalence of venous thromboembolism events in patients infected with severe acute respiratory syndrome coronavirus 2 requiring venovenous extracorporeal membrane oxygenation. The secondary objective was to compare venous thromboembolism events and coagulation variables in patients requiring venovenous extracorporeal membrane oxygenation according to the pathogen. DESIGN: Retrospective observational analysis at a single center. SETTING: Tertiary referral university teaching hospital. PATIENTS: Patients with severe acute respiratory syndrome coronavirus 2-related severe acute respiratory distress syndrome requiring venovenous extracorporeal membrane oxygenation therapy with an injected CT scan performed after extracorporeal membrane oxygenation retrieval. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: We included 13 severe acute respiratory syndrome coronavirus 2 patients requiring venovenous extracorporeal membrane oxygenation. All of these patients experienced venous thromboembolism: 10 patients (76.9%) had isolated cannula-associated deep vein thrombosis, two patients (15.4%) had isolated pulmonary embolism, and one patient (7.7%) had both cannula-associated deep vein thrombosis and pulmonary embolism. Eleven patients (84.6%) had cannula-associated deep vein thrombosis. A jugular associated cannula-associated deep vein thrombosis was identified in seven patients (53.8%), a femoral associated cannula-associated deep vein thrombosis was identified in 10 patients (76.9%), and six patients (46.2%) had both femoral and jugular cannula-associated deep vein thrombosis. A pulmonary embolism was found in three patients (23.1%). No patient had central venous catheter-related deep vein thrombosis. One patient had thrombotic occlusion of the centrifugal pump, and one had oxygenator thrombosis requiring circuit replacement. Three patients (23.1%) had significant bleeding. Three patients (23.1%) had laboratory-confirmed heparin-induced thrombocytopenia, and all of them developed cannula-associated deep vein thrombosis. These three patients had femoral cannula-associated deep vein thrombosis, and two had an oxygenator or pump thrombosis. The mean activated partial thromboplastin time ratio was higher in the severe acute respiratory syndrome coronavirus 2 group than in the influenza group and the community-acquired pneumonia group (1.91 vs 1.48 vs 1.53; p = 0.001), which was also found in regard to the percentage of patients with an activated partial thromboplastin time ratio greater than 1.8 (47.8% vs 20% vs 20.9%; p = 0.003) and the mean prothrombin ratio (86.3 vs 61.6 vs 67.1; p = 0.003). There was no difference in baseline characteristics or venous thromboembolism events. CONCLUSIONS: We report a 100% occurrence of venous thromboembolism in critically ill patients supported by venovenous extracorporeal membrane oxygenation for severe acute respiratory syndrome coronavirus 2-related acute respiratory distress syndrome using CT scan imaging despite a high target and close monitoring of anticoagulation.